Examining Maqasid Sharia Attainment: Case of Financing Products of Bank Muamalat Indonesia - Loni Hendri (Universitas Muhammadiyah Yogyakarta, 2021)
The objective of the Islamic Bank is still profit-oriented while the Islamic economy, as the mother of the Islamic Bank, has the orientation to obtain the maqasid sharia that agreed as social well-being, which can not always be obtained by profit alone. The first pure sharia Islamic Bank in Indonesia is Bank Muamalat. As the first bank purely shariah, Bank Muamalat commit to promoting services that not only comply with sharia but are also competitive and accessible for entire citizen. Based on this background, this research aimed to evaluate financing products of Bank Muamalat by using the framework of maqasid limited to aspect of justice. This research was descriptive-qualitative using secondary data such as financial statements, types of Bank Muamalat financing products acquired from the Bank Muamalat site and brochure. Results of this research showed that financing products of Bank Muamalat could be considered as the attainment of maqasid sharia because those products are dominantly provided in the equity-based contract. But, the conditions determined for the equity-based contract in Bank Muamalat’s financing products make them considered as not promoting maqasid sharia.